algebra

posted by .

(16x - 4y) - 10x + 5y)

  • algebra -

    ( 16 x - 4 y ) - ( 10 x + 5 y ) =

    16 x - 4 y - 10 x - 5 y =

    6 x - 9 y

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Intermediate Algebra

    Am I going in the right track? 8x -1/x + 5x - 3/2x = 16x^2 - 2x/2x^2 + 5x^2 - 3x/2x^2 16x^2 - 2x + 5x^2 - 3x/2x^2 =21x^2 - 5/2x^2 Find the LCD 6/7z- 28, 8/x^2 -4x = 7x(x-4) Simplify 3x^2 - 2x/15x-10 = x/5 Let's start by looking at
  2. algebra

    Solve the system by addition or substitution. 16x-4y=20 y=4x-4 I ask for help with this and forgot to add the problem. can anyone help me understand how to do this?
  3. Algebra

    There are two solutions to | 16x - 5 | = 3. The greatest solution is ___. Since the expression, 16x - 5, can be either positive or negative, solve for both. 16x - 5 = 3 16x = 8 x = .5 -(16x - 5) = 3 -16x + 5 = 3 -16x = -2 x = 1/8 You …
  4. Algebra II

    I honestly forgot how to do these type of problems. Can someone help me! Thanks!! -------------------------------------------------------------------------------------------- 24. ( 9x^2 - 4 )/( 3x^2 - 10x - 8 ) 31. 2x^2 + 5 = 12x 39. …
  5. algebra

    x^2 +16x+64 x^2+16x=64 (x=3)^2=16x-64 16x=-64 x=-4 Check this problem please
  6. math, really need some feedback asap.

    5/8 x+1/16 x=11/16+x 16*(5/8 x+1/16 x) = 16(11/16+x) 10x + x = 11 + 16x, so the next step is: 11x = 11 + 16x (get x-terms on the left.) -x = 11 (divide by -1.) x = 11 Is this correct?
  7. algebra

    use polynomial long division to divide -20x^3 -10x^2 -16x -8 by -5x^2 -4
  8. calculus

    i need to find the derivative using chain rule: (x^2 + 2x - 6)^2 (1-x^3)^2 i got the answer from a site but the problem is i cannot get my work to match up with the answer, i don't know what im doing wrong. answer: 10x^9 + 36x^8 − …
  9. Pre-Calculus

    Help please If f(x)=8x and g(x)=2x+1 find (fog)(x) 16x^2+8x 16x+1 16x+8 10x+1
  10. 9th grade algebra (completing square)

    Can you check the following? A1. (2x + 3)^2 = 25 sqrt(2x + 3)^2 = +-sqrt(25) 2x + 3 = +- 5 2x + 3 = 5, 2x + 3 = -5 2x = 2, 2x = -8 x = 1, x = -4 {-4, 1} A2. x^2 + 14x + 45 = 0 x^2 + 14x + __ = -45 + __ x^2 + 14x + 49 = -45 + 49 (x

More Similar Questions